Salivary Flow Rates in Various Occlusal Support Zones in Elderly Individuals - Kartika Indah Sari; Askani Maulida; Sri Tjahajawati (Journal of Indonesian Dental Association, 2021)
Introduction: Elderly individuals experience many changes in the oral cavity, one of which is tooth loss. Tooth loss disrupts the relationships between the maxillary and mandibular occlusions, which is detrimental to mastication. Mastication influences salivary secretion due to the salivary-masticatory reflex. Pressure on the teeth during mastication activates mechanoreceptors in the periodontal ligament, which can also stimulate salivary secretion. Objective: This study aimed to describe the salivary flow rates in various occlusal support zones in the elderly based on the Eichner Index. Methods: The study was cross-sectional and used a descriptive research method. The sample population comprised 36 elderly subjects residing in the village of Lebak Gede, Indonesia. Occlusal support zones were classified using the Eichner Index and stimulated salivary flow rates were measured using the Saxon test. Results: The sample population’s mean salivary flow rate was 1.35 ± 0.65 mL/min. The mean salivary flow rates for Eichner classifications A, B1, B2, and B3, were 1.56 ± 0.78 mL/min, 1.52 ± 0.56 mL/min, 1.18 ± 0.45 mL/min, and 0.95 ± 0.86 mL/min, respectively. Conclusion: The mean stimulated salivary flow rate tended to decrease as occlusal support zones decreased in Eichner classifications A, B1, B2, and B3.